Orthodoxy, Heresy and Treason in Elizabethan England - Claire Cross (Revue Française de Civilisation Britannique)
Between 1558 and 1570, Protestant and Catholic propagandists debated the claim of the English Church to be a true Church; after the excommunication of Elizabeth, the dispute moved on to whether Catholics were being executed for a political crime or sacrificing their lives for their faith. The irreconcilable positions of the two sides concerning orthodoxy, heresy, and treason form the subject of this essay.